Methods of criminology and criminal justice research - Deflem, Mathieu; Silva, Derek M. D. (Sociology of crime, law, and deviance, 2019)
The eleven chapters in this volume of Sociology of Crime, Law and Deviance discuss a variety of issues of methodological significance in research in the fields of criminology and criminal justice studies. As scholarly work on various aspects of crime, deviance, criminal justice, and social control has progressed tremendously in recent decades, both in terms of scope as well as with respect to theoretical approaches, the employed methods of investigation have also broadened and advanced to be as sophisticated as those used in any other area of contemporary social-science inquiry. The authors in this volume demonstrate the methodological maturity and diversity of current empirical research in criminology and criminal justice in a number of areas, such as general trends of crime, criminal networks, violence against women, sex work, elder financial exploitation, school safety, immigrant detention, extremism on the internet, and human trafficking.Presenting a state-of-the-art overview of criminological and criminal justice methodologies today, this book is of interest to a wide range of scholars and students in the fields of criminology, sociology, justice policy, and criminal justice.